Breaking New Ground in the Theory and Practice of Historical Lexicography - Vasyl Greshchuk (Vasyl Stefanyk Precarpathian National University, 2020)
Dydyk-Meush H. Kombinatoryka v ukrainskii movi ХVІ-ХVІІІ stolit: teoriia, praktyka, slovnyk. Lviv, Instytut ukrainoznavstva im. I. Krypiakevycha, Naukove tovarystvo im. Shevchenka, 2018.